2020
DOI: 10.1002/jcp.29813
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐36 receptor antagonist attenuates atherosclerosis development by inhibiting NLRP3 inflammasome

Abstract: Atherosclerosis is characterized, as an inflammatory disorder in the circulatory system, with increasing tendency toward mortality and morbidity. Thus, developing novel therapeutic targeting inflammation is necessary. Here, we investigated the effects of interleukin‐36 receptor antagonist (IL‐36RN), a newly identified anti‐inflammatory factor, on atherosclerosis. The regulation of NLRP3 inflammasome by IL‐36RN was determined in vitro in macrophage cells after oxidized low‐density lipoprotein (ox‐LDL) stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In atherosclerosis, macrophages play a central role in the initiation, growth, and final rupture of arterial plaque. Various studies based on different purposes have fully proved the vital role of macrophage inflammasome activation in the pathogenesis of atherosclerosis ( Tang et al, 2019 ; Yin et al, 2019 ; Tian et al, 2020 ; Wang et al, 2020 ). NLRP3 inflammasome activation is considered to be a key catalyst for atherogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In atherosclerosis, macrophages play a central role in the initiation, growth, and final rupture of arterial plaque. Various studies based on different purposes have fully proved the vital role of macrophage inflammasome activation in the pathogenesis of atherosclerosis ( Tang et al, 2019 ; Yin et al, 2019 ; Tian et al, 2020 ; Wang et al, 2020 ). NLRP3 inflammasome activation is considered to be a key catalyst for atherogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…IL-36 cytokines promote NLRP3 activation and IL-23/IL-17 production, leading to kidney inflammation and fibrosis ( 44 ). Another study revealed that IL-36Ra protects from atherosclerosis by inhibiting NLRP3 activation, and IL-1β and caspase-1 p10 production ( 45 ). The level of NLRP3 activation increased in NA patients ( 119 ), and this was associated with the degree of neutrophil airway inflammation, disease severity, and steroid resistance in asthma patients ( 120 ).…”
Section: Il-36 In Human Asthmamentioning
confidence: 99%
“…A complex relationship exists among IL-36 cytokines, nod-like receptor family pyrin domain 3 (NLRP3), neutrophil extracellular traps (NETs) and autophagy. In vivo and in vitro experiments have demonstrated that IL-36α promotes the NLRP3 expression and activation in mouse renal tubular epithelial cells and macrophages ( 44 ), while IL-36Ra inhibits NLRP3 activation and reduces inflammation in a mouse model of atherosclerosis ( 45 ). NETs increase the expression of IL-36α and IL-36γ in human bronchial epithelial cells ( 46 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, interleukins are a family of cytokines strongly associated with chronic inflammation and atherogenesis. Some interleukins can have proatherogenic effects while fewer interleukins can have atheroprotective effects [197,[203][204][205][206][207][208]. These DNA methylation alterations in pathways associated with atherogenesis suggest a usefulness for DNA methylation based CVD biomarkers.…”
Section: Functional Analysis Of Differentially Methylated Genes In Cvdmentioning
confidence: 99%